NOTE-TAKING DRILLING TO IMPROVE ACADEMIC LISTENING SKILLS IN THIRD SEMESTER STUDENTS, UNIVERSITAS MUHAMMADIYAH SURAKARTA: Received: 11th January 2022; Revised: 15th March 2022, 29th March 2022, 23rd April 2022; Accepted: 09th May 2022 - Mujazin, .; Mandiri, Angger Septo; Pratiwi, Ulya Septiana (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This study aims to reveal the role of note-taking in improving listening skills and exposing learning resources besides TED.COM. The skill of note-taking in academic activities is subject to the incompetency of note-taking in standard form. This research was a classroom action research approach for third-semester students at the Universitas Muhammadiyah Surakarta that focused on TED.COM’s contribution to students’ skills. The results of the initial research found obstacles, first, students were getting to know note-taking and TED.COM for the first time. Second, the high speed of native speakers impacts lost vocabulary understanding. Third, the tone, accent, and intonation are also separate challenges. The results of the cycles showed first, there was a positive change since the students got an extra note-taking theory and variations of audio listening. Second, students have varied learning resources, so it is recommended for educators to also understand student learning resources. In conclusion, TED.COM contributed to the academic listening improvement and in the future, the Podcast program can be explored for note-taking drilling besides TED.COM.